GPS Data Correction Based on Fuzzy Logic for Tracking Land Vehicles - Correa-Caicedo, Pedro J; Méndez-Gurrola, Iris Iddaly; Rostro-González, Horacio; Rodriguez-Licea, Martin A; Gutiérrez-Frías, Óscar Octavio; Herrera-Ramírez, Carlos Alonso; Cano-Lara, Miroslava; Barranco-Gutiérrez, Alejandro I (2021)
GPS sensors are widely used to know a vehicle’s location and to track its route. Although GPS sensor technology is advancing, they present systematic failures depending on the environmental conditions to which they are subjected. To tackle this problem, we propose an intelligent system based on fuzzy logic, which takes the information from the sensors and correct the vehicle’s absolute position according to its latitude and longitude. This correction is performed by two fuzzy systems, one to correct the latitude and the other to correct the longitude, which are trained using the MATLAB ANFIS tool. The positioning correction system is trained and tested with two different datasets. One of them collected with a Pmod GPS sensor and the other a public dataset, which was taken from routes in Brazil. To compare our proposal, an unscented Kalman filter (UKF) was implemented. The main finding is that the proposed fuzzy systems achieve a performance of 69.2% higher than the UKF. Furthermore, fuzzy systems are suitable to implement in an embedded system such as the Raspberry Pi 4. Another finding is that the logical operations facilitate the creation of non-linear functions because of the ‘if else’ structure. Finally, the existence justification of each fuzzy system section is easy to understand.